PENGARUH MODEL PROBLEM BASED LEARNING TERINTEGRASI JOYFUL LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI ELASTISITAS KELAS XI DI SMA NEGERI 2 PEMATANGSIANTAR - ANDRIONO MANALU (JURNAL ILMIAH KOHESI, 2019)
This study aims to determine the effect of Joyful Learning integrated Problem Based Learning models on student learning outcomes in the Elasticity and Hooke Law Class XI material at SMA Negeri 2 Pematangsiantar in the Academic Year 2019/2020. This type of research is the research used is a pre-experimental design with One Group Pretest-Posttest Design. The study population is all students of class XI PMIA in SMA 2 Pematangsiantar 2019/2020 Academic Year. Sampling was carried out by using the Random Sampling Cluster technique, the research sample was obtained, class XI PMIA-2 as an experimental class consisting of 35 students. The research instrument used was a student learning achievement test with multiple choice forms that had been tested by content validation by 2 validators with an average score of 4. After the treatment, an average grade of experimental class post-test with an average value of 77.29 was obtained. Increasing the average value of N-gain student learning outcomes in the experimental class is 0.68 with moderate criteria. The results showed that the integrated Joyful Learning Problem Based Learning model had a significant effect and was able to improve the learning outcomes of Grade XI students on Elasticity material in SMA Negeri 2 Pematangsiantar.